2016
DOI: 10.3171/2015.7.spine15201
|View full text |Cite
|
Sign up to set email alerts
|

Mobile spine chordoma: results of 166 patients from the AOSpine Knowledge Forum Tumor database

Abstract: OBJECT A chordoma is an indolent primary spinal tumor that has devastating effects on the patient's life. These lesions are chemoresistant, resistant to conventional radiotherapy, and moderately sensitive to proton therapy; however, en bloc resection remains the preferred treatment for optimizing patient outcomes. While multiple small and largely retrospective studies have investigated the outcomes following en bloc resection of chordomas in the sacrum, there have be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
87
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 99 publications
(88 citation statements)
references
References 21 publications
0
87
1
Order By: Relevance
“…We commend the authors for performing this interesting study as these helpful results would be useful to make a balanced treatment decision. However, we noted that the authors did not find extent of tumor invasion or worse preoperative Frankel score to be an independent predictor, which contradicts the results from previous studies …”
Section: Characteristics Of Included Studiescontrasting
confidence: 99%
See 1 more Smart Citation
“…We commend the authors for performing this interesting study as these helpful results would be useful to make a balanced treatment decision. However, we noted that the authors did not find extent of tumor invasion or worse preoperative Frankel score to be an independent predictor, which contradicts the results from previous studies …”
Section: Characteristics Of Included Studiescontrasting
confidence: 99%
“…However, we noted that the authors did not find extent of tumor invasion or worse preoperative Frankel score to be an independent predictor, which contradicts the results from previous studies. [2][3][4][5] To date, an increasing number of clinical and histopathologic factors as well as molecular biomarkers have been investigated for their association with spinal chordoma prognosis, 6 but the results are still inconclusive or controversial. We previously performed a systematic review on prognostic factors in spinal chordoma, 6 but no definitive conclusions could be derived due to heterogeneity and the scarcity of included studies.…”
Section: Dear Editormentioning
confidence: 99%
“…Surgical resection is the standard therapy for chordoma, though there have been recent advances in radiation therapy (RT). [6][7][8][9][10][11] En bloc surgical resection with negative margins and no intraoperative spill is associated with a reduced rate of local recurrence. However, the location of the chordoma may limit the ability to perform a gross total resection.…”
mentioning
confidence: 99%
“…3,4,6,7,9,13,17,20,25,27,34,39,[42][43][44]49,55 While en bloc resection is the treatment of choice for chordoma, not all chordomas are conducive to en bloc resection to achieve marginal or wide margins due to their relationship to other vital structures such as the spinal cord or vertebral arteries. 23,31 However, some authors have argued that aggressive resection is indicated even in the face of severe neurological sacrifice. With up to 32% of reported chordomas arising in the mobile spine, there remains a need to explore alternatives to traditional en bloc treatment in such complex cases with unique anatomical constraints.…”
mentioning
confidence: 99%